Evaluasi Program Talent Scouting Dalam Rekrutmen dan Pengembangan Personel TNI Angkatan Laut - Yuni Ratnasari; Edvien Adi Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
The talent scouting program is an important strategy in recruiting and developing personnel to ensure that organizations, including the Indonesian Navy, have quality human resources and are able to face modern challenges effectively. This research aims to explore the effectiveness of talent scouting programs in the context of the Indonesian Navy to identify and develop potential talents. This research aims to evaluate the relationship between talent selection methods, information sources, supporting technology, and development programs on the quality of Indonesian Navy personnel recruited through the talent scouting program. This study uses a quantitative approach by analyzing data from 55 respondents involved in the Indonesian Navy's talent scouting program. Data was collected through surveys using structured questionnaires, and analyzed using statistical techniques such as simple linear regression to evaluate the relationship between the variables studied. The results of the analysis show that talent selection methods and information sources have a significant influence on the quality of Indonesian Navy personnel (beta coefficients 0.62 and 0.58, respectively, t = 3.75, p = 0.002 and t = 4.21, p = 0.001). However, assistive technology showed a less significant effect (beta coefficient = 0.35, t = 1.80, p = 0.087). The development program was found to have a significant positive impact on personnel quality (beta coefficient = 0.70, t = 4.55, p = 0.000). The regression results show that the overall model is significant (F = 6.21, p = 0.001), confirming the importance of the variables studied in improving the quality of Indonesian Navy personnel through talent scouting programs.